Mergers & acquisitions in the lodging industry - a case study on the acquisition of ITT corporation by starwood hotels & resorts worldwide inc. - Ho, Emily Wei Leng. (2008)
This report examines the various studies being done on M&A. Based on these studies, we proceed to analyse a real life acquisiiton case.